Procyclicality or reverse causality? - Dany Jaimovich; Ugo Panizza (Inter-American Development Bank, Research Department, 2007)
There is a large literature showing that fiscal policy is either acyclical or countercyclical in industrial countries and procyclical in developing countries. Most of this literature is based on OLS regressions that focus on the correlation between a fiscal variable (usually the budget balance or expenditure growth) and either GDP growth or some measure of the output gap. This paper argues that such a methodology does not permit the identification of the effect of the business cycle on fiscal policy and hence cannot be used to estimate policy reaction functions. The paper proposes a new instrument for GDP growth and shows that, once GDP growth is properly instrumented, procyclicality tends to disappear.
Keywords: E62; E32; H62; 330; Fiscal Policy; Business Cycle; Emerging Markets